The Freckleton, England, air disaster : the B-24 crash that killed 38 preschoolers and 23 adults, August 23, 1944 - Hedtke, James R. (McFarland & Company, Inc., Publishers, 2014)
"The Freckleton catastrophe of August 23, 1944, occurred when an American B-24 Liberator crashed into the small village of Freckleton in north west England. The village would never be the same. In a compelling account of sorrow, loss, hope and finally rebirth, the book looks at the history of the village"--